Design of Web-Based Applications in Agrotourism Information Systems Using the SWOT Analysis Method - Ipang Sasono; Riyanto Riyanto; Suroso Suroso; Mustar Aman; Joni Iskandar (Universitas Bina Darma, 2023)
The Tangerang Regency Agrotourism represents a community-oriented recreational park designed for tourism. However, the existing information system for Tangerang Regency Agrotourism is non-web-based and lacks integration with modern information technology, leading to suboptimal processing of Agrotourism-related data. This research aims to assess the current system and develop a web-based agro-tourism information system for Tangerang Regency. The primary goal is to fulfill user requirements and aid governmental efforts in presenting park and tourist attraction information through a SWOT analysis-driven approach. The predicament faced by Tangerang Regency Agrotourism revolves around its reliance on non-integrated Microsoft Office applications for data processing, resulting in a lack of computerization. Employing qualitative research methodology, this study employs object-oriented system design techniques alongside the Unified Modeling Language. Consequently, the outcome of this research is the successful creation of a web based Agrotourism information system application tailored for Tangerang Regency's unique needs.